Educação ambiental e políticas públicas: a Baía de Guanabara e o boto-cinza - Cruz, Luciano Corado (2007)
The Guanabara Bay interacts with a great part of Rio de Janeiro metropolitan region and represents one of the most impacted coastal ecosystems of Southwestern Atlantic Ocean. Since the environmental degradation is mainly caused by human populations, Environmental Education activities turn out to be indispensable, although public politics for their promotion are still incipient. The objective of this dissertation was to identify the programs and different conceptions of Environmental Education used by the government in the Guanabara Bay area, besides the possibilities and limits of its incidence on the student s perception, in the perspective of the construction of a critical vision about the environment. A theoretical reference picture was constructed based on the identification of different Environmental Education conceptions, and was used as a reference tool for a critical analysis of Environmental Education public programs developed by the three levels of government in the Guanabara Bay region, and for the assessment of a methodological proposal that had the coastal dolphin as symbol species of the Guanabara Bay conservation. This work was developed with students of 4th series of the fundamental level, in three public schools located at the Guanabara Bay shore. The possibilities of methodological proposal be improved in large scale by governments with methods of attendance that allow the evaluation of their results was discussed. This work may give a contribution to a critical analysis of conceptions and experiences that take place at school, and to the development of Environmental Education public programs that aim at a critical education of humans concerned and engaged with the life preservation and the environmental sustainability